2003
DOI: 10.1097/01.asn.0000060578.79050.e0
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the Spectrum of Diseases Related to Podocin Mutations

Abstract: Abstract. A total of 179 children with sporadic nephrotic syndrome were screened for podocin mutations: 120 with steroid resistance, and 59 with steroid dependence/frequent relapses. Fourteen steroid-resistant patients presented homozygous mutations that were associated with early onset of proteinuria and variable renal lesions, including one case with mesangial C3 deposition. Single mutations of podocin were found in four steroid-resistant and in four steroid-dependent; five patients had the same mutation (P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
156
3
14

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(184 citation statements)
references
References 29 publications
11
156
3
14
Order By: Relevance
“…This variant was absent in 54 white control subjects and was predicted to be probably pathogenic by the software PolyPhen (http://www.bork.embl-heidelberg.de/ PolyPhen/). In addition, we found several sequence variants of uncertain significance (A41G, E310K, E237Q, and IVS3 ϩ 3InsA) as well as several previously reported neutral polymorphisms (G102A, G34G, C288T, S96S, A242V, T954C, A318A, A1038G, and L346L) (27)(28)(29)(30)32). Among the entire study cohort, we found recessive mutations in only one patient.…”
Section: Nphs2 Mutation Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…This variant was absent in 54 white control subjects and was predicted to be probably pathogenic by the software PolyPhen (http://www.bork.embl-heidelberg.de/ PolyPhen/). In addition, we found several sequence variants of uncertain significance (A41G, E310K, E237Q, and IVS3 ϩ 3InsA) as well as several previously reported neutral polymorphisms (G102A, G34G, C288T, S96S, A242V, T954C, A318A, A1038G, and L346L) (27)(28)(29)(30)32). Among the entire study cohort, we found recessive mutations in only one patient.…”
Section: Nphs2 Mutation Analysissupporting
confidence: 78%
“…Indeed, homozygous or compound heterozygous NPHS2 mutations have been documented in 30 to 46% of familial and 10 to 30% of sporadic steroid-resistant nephrotic syndrome in older children (26 -30). Typically, FSGS is the most common pathology associated with these cases, although a spectrum of glomerular lesions, including mesangial proliferation and minimal-change lesion, also may be seen (27,28). To define further the clinical relevance of NPHS2 mutations, we undertook a comprehensive mutation screening study in 87 cases of adult-onset idiopathic FSGS.…”
mentioning
confidence: 99%
“…Presence of pathological signs of cyclosporine nephropathy (tubulointerstitial fibrosis, epithelia vacuolization, calcineurin inhibitors crystals) (4) Deterioration of renal function in the last 6 months (20% increase of serum creatinine levels) NMR, nuclear magnetic resonance.…”
Section: Steroidsmentioning
confidence: 99%
“…INS affects 2 to 2.7 new children per 100,000 children per year, in Western countries, with a prevalence of 16 cases per 100,000 children (1). Mechanisms underlying the disorder include different genetic and pathologic variants (2)(3)(4), with polymorphic podocyte injury as a unifying feature (5-7). All described phenotypes are considered part of a pathology continuum from minimal lesions (minimal change disease) to podocyte depletion and glomerulosclerosis (focal and segmental glomerular sclerosis) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: BMI: body mass index, CHD: coronary heart disease, HDL: high-density lipoprotein cholesterol, ACR: albumin-to-creatinine ratio, eGFR: estimated glomerular filtration rate, NC. Covariates missing: hypertension (13), diabetes (14), BMI (4), smoking (7), CHD (72), HDL (7), triglycerides (7), ACR (31), eGFR (7). To convert HDL in mg/dl to mmol/l, multiply by 0.0259, triglycerides in mg/dl to mmol/l, multiply by 0.0113; eGFR in ml/min/1.73m 2 to ml/s, multiply by 0.0167.…”
Section: Supplementary Materialsmentioning
confidence: 99%